2011
DOI: 10.1007/s12550-011-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in foods in Lower Saxony (Germany): results of official control analyses performed in 2009

Abstract: In this presentation, the mycotoxin levels-as analysed by the analytical centre for mycotoxin surveillance of the state food laboratory (LAVES Braunschweig)-for approximately 500 food samples are reported. The samples were collected in the year 2009 at retail in the German federal state of Lower Saxony. Aflatoxin and ochratoxin A were analysed in dried fruits, spices, cereals and tree nuts. Ochratoxin A was detected in all samples of dried vine fruits, at levels up to 8.1 μg/kg. Aflatoxins and ochratoxin A wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
1
15
1
2
Order By: Relevance
“…was found to be a predominant fungal infection in chilli (Reddy et al 2001). AFs contamination in several kinds of spices has been reported elsewhere (Cho et al 2008;Reinhold & Reinhardt 2011). Among monitoring of spices in the Irish market, chilli powder was found to be contaminated with AFs (range 0.35-27.50 µg kg −1 ) in higher concentrations than others (O'Riordan & Wilkinson 2008).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…was found to be a predominant fungal infection in chilli (Reddy et al 2001). AFs contamination in several kinds of spices has been reported elsewhere (Cho et al 2008;Reinhold & Reinhardt 2011). Among monitoring of spices in the Irish market, chilli powder was found to be contaminated with AFs (range 0.35-27.50 µg kg −1 ) in higher concentrations than others (O'Riordan & Wilkinson 2008).…”
Section: Introductionmentioning
confidence: 78%
“…The authors reported AF levels between 0.1 and 50.7 µg kg −1 . In 2010, AFs were found in more than 70% of the 22 analysed basmati rice samples in Germany with a mean concentration of 1.53 µg kg −1 (Reinhold & Reinhardt 2011). In Canada, two years study of AFs contamination in rice reported mean values of 0.34-0.39 µg kg −1 in AFB1 (with a maximum level of 7.14 µg kg −1 ).…”
Section: Occurrence Of Aflatoxins In Rice Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the LOQ of our method is considerably lower than that used in the above cited works (ZEA LOQ = 0.012 ng/g vs. higher than 0.5 ng/g). However, in another study where the authors analyzed samples of maize flour from the German market, they found that 62.5% of the samples were contaminated with ZEA, with a median concentration value of 12 ng/g (Reinhold and Reinhardt, 2011). It is likely that these higher concentrations reported in German flour are due to the fact that they come from unroasted cereal.…”
Section: Occurrence Of Mycotoxins In Gofiomentioning
confidence: 99%
“…Generally it is possible to remove up to 82 % of ergot by mechanical means with conventional grain cleaning equipment such as sieves and separators used during the harvesting process. But despite these cleaning procedures, different surveys have demonstrated that ergot alkaloids can still be present in cereal-based food and feed, sometimes in excessive amounts (Crews et al, 2009;Diana Di Mavungu et al, 2011;Malysheva et al, 2014;Lombaert et al, 2003;Müller et al, 2009;Reinhold and Reinhardt, 2011).…”
Section: Introductionmentioning
confidence: 99%